Does debt increase risk? A mixed methods approach to studying the potential underlying risk factors in the relationship between debt and crime - van Beek, Gercoline (Psychology, crime & law, 2023)
Previous studies have found evidence for a relationship between debt and crime, and for problems in childhood, education, work, and mental and physical health as underlying risk factors. However, insight into the interplay between these possible risk factors is limited. Therefore, a mixed methods approach was applied by both creating a quantitative Gaussian Graphical Model (GGM) and conducting qualitative analyses on 250 client files including risk assessment data from the Dutch probation service, to gain more specific insight into the interaction between potential risk factors. The results show that debt is strongly related to criminal behavior and problems in many life domains for most probation clients. Debt seems to be a direct risk factor for crime, but debt and crime also appear to be highly interrelated as part of a complex interplay of risk factors. The most frequently rated factors – limited or incomplete education, no job and related lack of income, and mental and physical health problems – are highly interwoven and increase the risk of both debt and crime. The findings stress the importance of paying attention to and using interventions focusing on strongly related crime risk factors, including debt, and their complex interplay, to supervise probation clients effectively.